An ongoing search of constant and sustainable Lutheran Theological Education in South Africa in the 21st century - Mashabela, K. (Acta theologica, 2023)
This article explores the recent history of Lutheran theological education in South Africa, which is still confronted by the legacy of colonial and apartheid education systems. The latter need to be confronted with liberation and decolonisation systems that reclaim African indigenous identities. There is a need to cultivate a culture of quality and equal education, spirituality, politics, and socio-economic systems for the service of South Africans. Evangelical Lutheran churches inSouthern Africa are committed to improve and reform Lutheran theological education in the 21st century. Lutheran theological education is necessary to make a meaningful contribution towards training theological students to assist the church in its response to societal concern and contextual issues. The article introduces a recent renewal of Lutheran theological institutions in a new teaching and learning environment by the Lutheran Church. It discusses the implications and successes of Lutheran theological education in South Africa.